Further adventures of Lad. - Terhune, Albert Payson, 1872-1942. (New York, Grosset & Dunlap, 1961)
The exploits and achievements of the collie, Lad, from his routing of a burglar as a five-month-old puppy to his protection of a child from a cruel father, his last act as an aged sixteen-year-old dog.
Keywords: Dogs -- Juvenile fiction; Dogs -- Fiction